Development of Kodular Based Interactive Teaching Materials in Meeting Organizing Materials in SMK Negeri 2 Buduran - Nur Rizal Alfani; Durinda Puspasari (Dinamika Pendidikan, 2022)
This study describes the development of kodular-based interactive teaching materials in the essential competencies of holding meetings and making notes, analyzing the feasibility of teaching materials, analyzing student responses, and analyzing the effectiveness of using teaching materials to improve student learning outcomes at SMK Negeri 2 Buduran. This research is development research that refers to the 4D model: define, design, develop, and disseminate. Students from class XII OTKP 1 as the experimental class and class XII OTKP 2 as the control class were used as subjects and samples in this study. Material expert validation sheets, language, graphs, student response questionnaires, and student learning outcomes tests were all used as part of the data collection instrument. Expert validation of questions and materials, language, graphics, item analysis, N-Gain analysis, completeness of student learning outcomes, homogeneity test, normality test, and hypothesis testing are data analysis techniques used. The developed interactive teaching materials were scored in the appropriate category, with 87.6% material experts, 90.6 % linguists, and 94.2 % graphic experts, with the overall criteria assessed in the very decent range. Meanwhile, students' responses to the developed interactive teaching materials got a %age of 90.26% with excellent criteria. It can be concluded that the interactive teaching materials developed are effective as supporting teaching materials to improve student learning outcomes of SMK Negeri 2 Buduran in class XII OTKP.